Implementation of the PLAVON Dukcapil Program in Population Administration Services - Setyoningasih, Ari; Mursyidah, Lailul (Indonesian Journal of Cultural and Community Development, 2024)
The general background of this research highlights the increasing importance of e-government services in enhancing administrative efficiency and accessibility for citizens. The specific background focuses on the implementation of the PLAVON Dukcapil program, which is an online service initiative aimed at improving population administration services in a local government setting. The knowledge gap identified in this study pertains to the lack of comprehensive evaluation regarding the effectiveness of communication, resources, disposition, and bureaucratic structure in this program’s implementation. The aims of the research are to assess the operational aspects of the PLAVON Dukcapil program and to provide recommendations for improvement. The results reveal four key aspects affecting implementation: communication has not been optimized, resource placement needs attention, the village head's commitment is lacking, and while the bureaucratic structure follows established SOPs, continuous evaluation is necessary. The novelty of this study lies in its focus on qualitative descriptive analysis, providing insights into practical challenges faced by local administrators. The implications suggest that improvements in communication strategies, proper resource allocation, enhanced commitment from leadership, and ongoing evaluation of procedures are essential for the successful implementation of e-government services, ultimately leading to better community engagement and service delivery in population administration. Highlights: Communication strategies need improvement for better community understanding of PLAVON. Resource allocation and staff training are crucial for effective program implementation. Continuous evaluation of bureaucratic structures is necessary to enhance service delivery. Keywords: E-Government, PLAVON, Administration, Communication, Resources